LABOR MIGRATION ISSUES IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2026)
The article examines the root causes of international migration from Uzbekistan through the lens of demographic and socio-economic development. It focuses on the challenges of employing a growing population, infrastructure deficits in regions, and low-income levels in rural areas. The study concludes with recommendations aimed at creating conditions for legal and protected migration.